Inside the yield book : new tools for bond market strategy - Homer, Sidney; Leibowitz, Martin L. (London : Prentice-Hall International, Inc., 1972)
It skillfully explains and makes sense of essential mathematical relationships that are basic to an understanding of bonds, annuities, and loans.
Includes index
ucj 17/01/2019
Loans
Keywords: Bonds|zUnited States